2022
DOI: 10.1002/ags3.12580
|View full text |Cite
|
Sign up to set email alerts
|

Simple systemic index associated with oxaliplatin‐induced liver damage can be a novel biomarker to predict prognosis after resection of colorectal liver metastasis

Abstract: Aim: Oxaliplatin, an anticancer drug for advanced colorectal cancer, causes liver sinusoidal damage, sometimes with portal hypertension. We conducted a retrospective comparative study of the relationship of liver sinusoidal disorders and liver function with the prognosis in patients who underwent hepatectomy for colorectal liver metastasis (CRLM).Methods: In total, 158 patients who underwent hepatectomy for CRLM were included in the study, and the effect of chemotherapy-associated liver damage on the prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In some studies, the development of sinusoidal obstruction syndrome (SOS) has been shown in patients treated with oxaliplatin-containing regimens [6][7][8]. In another study by Ward et al, surgery-confirmed SOS was found in 24 of 60 patients who received neo-adjuvant oxaliplatin-based chemotherapy for over 12 weeks [9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the development of sinusoidal obstruction syndrome (SOS) has been shown in patients treated with oxaliplatin-containing regimens [6][7][8]. In another study by Ward et al, surgery-confirmed SOS was found in 24 of 60 patients who received neo-adjuvant oxaliplatin-based chemotherapy for over 12 weeks [9][10].…”
Section: Discussionmentioning
confidence: 99%